Demorest's Family Magazine - Demorest, William Jennings (New York: W.J. Demorest, 1883)
Some Funny Fruit; Agathe de Valsuze; "Can He Pass, and We Forget?" : A Modern Episode; The Inhabitants of Algiers; How We Live in New York: The Business Girl; The Modern Drama and its Possibilities; Which?; A Grave Under the Sea; The Alhambra; A Portrait; In White; The Bride of Lammermoor; My Lady: The Story of a Poor Rich Girl; Hereafter; Home Art and Home Comfort; A Thirsty Company; Valé; A Talk with the Young Ladies of Clifford; Margaret; Raking the Meadow Lot: A Hay-time Idyl; Martha's Experiment; How a Woman Loved and Trusted; My Ignis-Fatuus: Minnie!; At Dead of Night; What Women Are Doing; Table Spread; Sham Picture Gallery; Work Box; Foot Rest; The World's Progress; Kitchen; Scientific; Diamonds of Thought; Spice Box; Mirror of Fashions: Review of Fashions.-September; Paris Fashions; Illustrated Designs; Highland Dinner Dress; Autumn Costumes; Collarettes and Jabots; Dolores Mantelet; Lace Wraps and Dresses; Street Costume; Trains; Lawn Party Dresses; Between Seasons; Autumn Styles; School Dress; Misses' Costumes; Fashions for Children; Ladies' Club; The Tribune Fresh Air Fund; An Eastern Watering Place; An Owlish Appeal; This Picture and That; Review of New Publications; The Great Cotton Exposition; Good Words.-Texas; Beautiful Works of Arts; New Styles in Autumn Silks; A Useful Novelty; Daffodil Design for a Wall Hanging
Demorest's New York Illustrated News Mme.; Demorest's Quarterly Mirror of Fashions
Keywords: Women's History; Fashion; Periodicals; Dress Making < Periodicals; Magazines